Current Trends in Targeted Therapies for Glioblastoma Multiforme - Fumiharu Ohka; Atsushi Natsume; Toshihiko Wakabayashi (Neurology Research International)
Glioblastoma multiforme (GBM) is one of the most frequently occurring tumors in the central nervous system and the most malignant tumor among gliomas. Despite aggressive treatment including surgery, adjuvant TMZ-based chemotherapy, and radiotherapy, GBM still has a dismal prognosis: the median survival is 14.6 months from diagnosis. To date, many studies report several determinants of resistance to this aggressive therapy: (1) O6-methylguanine-DNA methyltransferase (MGMT), (2) the complexity of several altered signaling pathways in GBM, (3) the existence of glioma stem-like cells (GSCs), and (4) the blood-brain barrier. Many studies aim to overcome these determinants of resistance to conventional therapy by using various approaches to improve the dismal prognosis of GBM such as modifying TMZ administration and combining TMZ with other agents, developing novel molecular-targeting agents, and novel strategies targeting GSCs. In this paper, we review up-to-date clinical trials of GBM treatments in order to overcome these 4 hurdles and to aim at more therapeutical effect than conventional therapies that are ongoing or are about to launch in clinical settings and discuss future perspectives.